Comprehensive knowledge on cervical cancer, attitude towards its screening and associated factors among women aged 30-49 years in Finote Selam town, northwest Ethiopia - Alehegn Bishaw Geremew; Abebaw Addis Gelagay; Telake Azale (BMC, 2018)
Abstract Background Screening services for cervical pre-cancerous lesions is currently available for all women aged 30-49 years at public hospitals in Ethiopia. Though women's knowledge and their attitude are determinants for the uptake the screening service, there is limited information on these regards. Therefore, this study aimed to assess comprehensive knowledge on cervical cancer, attitudes towards the screening, and associated factors among women aged 30-49 years at Finote Selam town, northwest Ethiopia. Methods A community based cross-sectional study was conducted from March 30, to April 15, 2017. The sample size calculated for this study was 1224 and a cluster sampling technique was used to select the participants from three randomly selected kebeles. Epi-Info version 7 and Statistical Package for Social Sciences version 20 were used for data entry and analysis respectively. A binary logistic regression model was used. In multivariable logistic analysis, adjusted odds ratio with a 95% confidence interval was used to determine the presence and strength of associations between covariate and outcome variable. Results A total of 1137 women participated in this study. Nearly one third, 30.3% (95%CI: 27.7, 32.9) of the women had knowledge of cervical cancer, and 58.1% (95% CI: 55, 62.2) had a favorable attitude towards cervical cancer screening. In the multivariable analysis, having college and above education (AOR = 7.21, 95%CI: 3.41, 15.29), knowing someone with cervical cancer (AOR =5.38, 95%CI: 2.38, 12.15), and having a history of sexually transmitted diseases (AOR = 2.75, 95%CI: 1.24, 6.04) were significantly associated with knowledge on cervical cancer. Meanwhile, college and above educational status (AOR = 2.56, 95%CI: 1.14, 5.69), knowing someone with cervical cancer (AOR = 3.24, 95%CI: 1.14, 9.15), and having knowledge of cervical cancer (AOR = 3, 95%CI: 1.97, 4.29) were positively associated with favorable attitudes towards cervical cancer screening. Conclusion The proportion of women who had knowledge on cervical cancer was low where as relatively, a large proportion of the study participants in this study had favorable attitude towards cervical cancer screening. Educational status, knowing someone with cervical cancer, a history of sexually transmitted diseases was factors affecting both women's knowledge and their attitude. Having knowledge on cervical cancer was factor affecting attitude towards screening services. Provision of information, education, and counseling about the disease and screening service are mandatory to address their knowledge gap and to improve women's attitude towards screening service.